Ni/Fe Ratio Dependence of Catalytic Activity in Monodisperse Ternary Nickel Iron Phosphide for Efficient Water Oxidation. Issue 9 (21st June 2017) - Tang, Kai; Wang, Xianfu; Wang, Mengfan; Xie, Yiming; Zhou, Jinqiu; Yan, Chenglin
Abstract: Electrochemical water splitting is an effective way to obtain hydrogen fuel as a clean and renewable energy source. However, a major challenge is to accelerate the sluggish oxygen evolution reaction (OER) kinetics with a multistep proton‐coupled electron‐transfer process. Transition metal Ni‐ and Co‐based composites have been developed to replace expensive and scare noble metal based OER catalysts. So far, layered NiFe double hydroxide represents the best OER activity among all Ni‐ and Co‐based oxides. Herein, monodispersed ternary (Ni1‐ x Fe x )12 P5 nanocrystalline materials with tunable Ni/Fe ratios are reported as highly efficient OER electrocatalysts, exhibiting activity and stability surpassing noble metal OER catalysts including RuO2, IrO2, and superior to nickel phosphides, layered nickel‐iron double hydroxides, and other NiFe‐based OER catalysts. X‐ray photoelectron spectroscopy (XPS) studies reveals that enhanced charge transfer from the foreign metal (Fe) to the host (Ni) to P atoms and a strong synergistic effect exist in the composite (Ni1‐ x Fe x )12 P5 electrocatalysts, thus rendering the as‐prepared (Ni1‐ x Fe x )12 P5 nanocrystalline compounds (NCs) with a Ni/Fe ratio of 0.51/0.49, the highest OER activity with a small onset potential of 125 mV, a low Tafel slope of 39 mV dec −1, and a low overpotential of 216 mV, to achieve 20 mA cm −2 in an alkaline medium electrolyte (1.0 M KOH). Abstract : From one to another : Monodisperse ternary (Ni1‐ x Fe x )12 P5 electrocatalysts with a controlled Ni/Fe ratio for efficient oxygen evolution reaction are reported. These materials demonstrate a superior catalytic activity originating from the enhanced charge transfer from the foreign metal (Fe) to the host (Ni) to P atoms.